Developing a Preliminary Checklist for Vocabulary Task Evaluation - Manal Laaribi (Journal of Languages and Language Teaching, 2022)
Language teachers are usually provided with textbook material that contains several tasks and activities. Although these activities are meant to facilitate the learning and teaching processes, it is important to approach the provided material critically, make the necessary adjustments to its components, and contextualize its themes. The use of a checklist may render this process of adopting and adapting material feasible and effective since a checklist provides a practical systematic approach to analysis. This paper will provide the reader with a preliminary design of a checklist for vocabulary task evaluation that includes a 5-point Likert scale and contains eight main items and twenty-two sub-items that represent some of the main principles of vocabulary learning. These principles have been incorporated into the checklist on the basis of relevant literature and perspectives of different researchers, experienced teachers, and teacher trainers. This paper will also provide the reader with a demonstration of the use of this checklist through the analysis of a unit’s vocabulary section of the book “Gateway to English 2.”